Factors associated with four or more antenatal care services among pregnant women: a cross-sectional survey in eight South Central Coast provinces of Vietnam - Ha BTT; Tac PV; Duc DM; Duong DTT; Thi LM (Dove Medical Press, 2015)
Bui TT Ha,1 Pham V Tac,2 Duong M Duc,1,3 Doan TT Duong,1 Le M Thi1 1Department of Reproductive Health, Hanoi School of Public Health, 2Department of Personnel and Organization, Ministry of Health, Ba Dinh, Ha Noi, Vietnam; 3International Maternal and Child Health (IMCH), Department of Women’s and Children’s Health, Uppsala University, Uppsala, Sweden Background: In Vietnam, four or more antenatal care (ANC4+) visits/services among pregnant women have not been officially reported in the health system. Moreover, the factors associated with the use of ANC4+ services have not been studied in previous studies. In this study, we conducted an exploratory analysis to identify the rate of utilization of ANC4+ services and factors associated with use of ANC4+ services among pregnant women in rural areas of Vietnam.Methods: The study was conducted in eight provinces in the South Central Coast region of Vietnam between August 2013 and May 2014. A total of 907 women, who delivered in the past 1 year, participated in the study. Multivariate logistic regression model was used to examine the association between all potential factors and utilization of ANC4+ services.Results: The rate of utilization of ANC4+ services by women in eight South Central Coast provinces was 53.9%. Factors negatively associated with using ANC4+ services were belonging to ethnic minority groups having lower education, doing informal works, having lower income, having lower knowledge on ANC4+ services, and receiving no financial support from the husband. In particular, financial support from the husband was considered important in improving the use of ANC4+ services by women in rural areas.Conclusion: The study asserted an inadequacy for ANC4+ utilization and can contribute to missed opportunities to achieve better maternal outcomes for women in rural areas of Vietnam. The necessity of introducing ANC4+ services in the national guidelines on maternal health care should be disseminated to health policy-makers. Strategies to increase ANC4+ utilization should focus on knowledge improvement and on poor, low-income, and ethnic minority women. Keywords: pregnant women, antenatal care services, ethnic minority, male involvement, South Central Coast provinces, Vietnam